THE IMPLEMENTATION OF LEARNING STRATEGIES TO MAINTAIN ENGLISH SPEAKING PERFORMANCE IN POST-FORMAL STUDY PERIOD - Kurniawan, Erwin; Salam, Uray; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMany types of learning strategies can be used by the language learners to make the learning process running well. However, in doing the practice the learners are identified limited types of learning strategies and it makes them face many problems in learning. The aims of the study is to find the typical learning strategies used by the Alumnus of English Education Study Program of Teacher Training and Education Faculty Tanjungpura University in speaking English. The result of the study showed that the alumnus of English Education Study Program of Teacher Training and Education Faculty Tanjungpura University used singing english song, exploring a book, and watching western movies as the activities to employ her speaking skill and from that activity she can develop her speaking skill. Thus, the learner of English Department are suggested to ap ply many strategies. For this reasearch the socio- affective strategies should be the most suitable strategy practiced by the alumni. Keywords: Learning strategies, Post formal study, Speaking Performance